Characteristics associated with mortality in patients with chronic obstructive pulmonary disease (COPD)–heart failure coexistence. Issue 6 (21st February 2018) - Plachi, Franciele; Balzan, Fernanda M.; Sanseverino, Renata A.; Palombini, Dora V.; Marques, Renata D.; Clausell, Nadine O.; Knorst, Marli M.; Neder, J. Alberto; Berton, Danilo C.
Abstract: Aim: To investigate if cardiac/pulmonary functional tests and variables obtained from clinical practice (body mass index, dyspnea, functional class, clinical judgment of disability to perform an exercise test and previous hospitalization rate) are related to mortality in patients with overlap chronic obstructive pulmonary disease (COPD) and chronic heart failure (CHF). Background: Although the coexistence of COPD and CHF has been growingly reported, description of survival predictors considering the presence of both conditions is still scarce. Methods: Using a cohort design, outpatients with the previous diagnosis of COPD and/or CHF that performed both spirometry and echocardiography in the same year were followed-up during a mean of 20.9±8.5 months. Findings: Of the 550 patients initially evaluated, 301 had both spirometry and echocardiography: 160 (53%) with COPD on isolation; 100 (33%) with CHF on isolation; and 41 (14%) with overlap. All groups presented similar mortality: COPD 17/160 (11%); CHF 12/100 (12%); and overlap 7/41 (17%) ( P =0.73). In the overlap group ( n =41), inability to exercise and hospitalization rate were the unique parameters associated with higher mortality (seven events) in univariate analyses. In conclusion, inability to exercise and hospitalization rate emerged as the unique parameters associated with mortality in our sample.